2010
DOI: 10.1158/1078-0432.ccr-10-0142
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Maintenance and DNA Damage Responses during Lung Carcinogenesis

Abstract: Purpose: Telomere shortening is an early event in bronchial carcinogenesis, preceding P53/Rb pathway inactivation and telomerase reactivation, and leading to DNA damage responses (DDR). As their inactivation in cancer increases genetic instability, our objective was to identify the chronology of telomere machinery critical events for malignant progression.Experimental Design: We have evaluated telomere length by fluorescence in situ hybridization and analyzed DDR proteins p-CHK2, p-ATM, and p-H2AX, and telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…As expected, oxidative DNA damage is prominent in COPD lungs [53,54]. The expression of DNA damage/repair proteins also increases significantly with worsening severity of the pre-neoplastic changes in the lung [55], further strengthening the hypothesis that oxidative DNA damage is important in lung carcinogenesis. Since NSCLC originates from bronchial epithelial cells or the terminal respiratory unit, it was thought that COPD-related molecular differences in the epithelium would be magnified in NSCLC because of clonal expansion [56].…”
Section: Oxidative Stress and Inflammation As The Link Between Copd Asupporting
confidence: 67%
“…As expected, oxidative DNA damage is prominent in COPD lungs [53,54]. The expression of DNA damage/repair proteins also increases significantly with worsening severity of the pre-neoplastic changes in the lung [55], further strengthening the hypothesis that oxidative DNA damage is important in lung carcinogenesis. Since NSCLC originates from bronchial epithelial cells or the terminal respiratory unit, it was thought that COPD-related molecular differences in the epithelium would be magnified in NSCLC because of clonal expansion [56].…”
Section: Oxidative Stress and Inflammation As The Link Between Copd Asupporting
confidence: 67%
“…Telomere attrition occurs at the earliest stage of lung carcinogenesis as an initiating event [20]. In CRCs, various studies demonstrated that telomeres were shorter in tumor samples than in adjacent normal mucosa [11,21], but this finding was not confirmed by other studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of telomere repeats diminishes telomeric functional capacity and has been associated with the development of hematologic and solid tumor malignancies (1, 2). Recent studies have noted shortened telomeres in prema lignant or dysplastic tissues and in “normal” epithelium adjacent to tumors (field defect) supporting the contribution of telomeric shortening to early carcinogenesis (36). It is also well established that upon full malignant transformation, the majority of tumors have engaged mechanisms to abnormally lengthen telomeres.…”
Section: Introductionmentioning
confidence: 93%